2014
DOI: 10.1111/jdi.12260
|View full text |Cite
|
Sign up to set email alerts
|

Response to the dipeptidyl peptidase‐4 inhibitors in Japanese patients with type 2 diabetes might be associated with a diplotype of two single nucleotide polymorphisms on the interleukin‐6 promoter region under a certain level of physical activity

Abstract: Aims/IntroductionMuscle-derived interleukin-6 (IL-6) has been reported to promote glucagon-like peptide-1 (GLP-1) secretion, and we explored the association of single nucleotide polymorphisms (SNPs) in the human IL-6 promoter region with the responsiveness to dipeptidyl peptidase-4 inhibitors (DPP-4Is), drugs that increase circulating GLP-1.Materials and MethodsThe present observational study enrolled Japanese patients with type 2 diabetes who took a DPP-4I over 3 months, and most of the clinical information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…Matsui et al performed a study on the effects of SNPs in the IL6 promoter region on response to DPP4I. The results showed that diplotype rs1800796 allele G and rs2097677 allele A might contribute to DPP4I responsiveness in case the carrier is physically active [ 130 ].…”
Section: Genes Associated With Dpp4-inhibitors and Glp1 Receptor Amentioning
confidence: 99%
“…Matsui et al performed a study on the effects of SNPs in the IL6 promoter region on response to DPP4I. The results showed that diplotype rs1800796 allele G and rs2097677 allele A might contribute to DPP4I responsiveness in case the carrier is physically active [ 130 ].…”
Section: Genes Associated With Dpp4-inhibitors and Glp1 Receptor Amentioning
confidence: 99%
“…[ 23 ] On the other hand, an association between interleukin-6 polymorphism and DPP-4 inhibitor response has been reported. [ 24 ] Recent preclinical studies have shown association between DPP-4 inhibitors and incretin receptors. [ 25 , 26 ] Since administration of DPP-4 inhibitor to incretin receptor knockout mice did not improve glycemic parameters, these findings suggest the importance of incretin receptor in glucoregulatory actions of DPP-4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Because the renal function of these six healthy subjects was normal, the variability of vildagliptin cyano group-hydrolyzing activity might have caused the interindividual variability in C max and AUC of vildagliptin. There are nonresponders to vildagliptin, who do not show any significant decrease of hemoglobin A1c (Nakamura and Terauchi, 2013;Matsui et al, 2015). Additionally, vildagliptin can cause rare but serious adverse reactions, such as liver injury (Deacon, 2011;Kurita et al, 2014), bullous pemphigoid (Béné et al, 2015;Mendonça et al, 2016), and interstitial pneumonia (Kuse et al, 2016), in patients.…”
Section: Discussionmentioning
confidence: 99%